2005
DOI: 10.1177/097133360501700207
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Status of South Asian Women in Britain

Abstract: Mental Health of South Asian Women in Britain / 195 This article reviews the research on the mental health status of South Asian women living in UK. It reports on the findings from epidemiological studies of the prevalence of depression, suicide, parasuicide, deliberate self-harm and eating disorders in this community. Focus is on research studies that describe cultural influences on conceptualisations and expressions of distress, help seeking behaviours and alternative coping strategies. The influence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 43 publications
2
48
1
1
Order By: Relevance
“…After observing the numerous cultural and linguistic barriers that Pakistani women face when engaging in enterprise in the UK, Duncan organised a new 3-year study to investigate the impact of social and community relations on the women's worldview (see Anand and Cochrane, 2005;Platt, 2007;Gater et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…After observing the numerous cultural and linguistic barriers that Pakistani women face when engaging in enterprise in the UK, Duncan organised a new 3-year study to investigate the impact of social and community relations on the women's worldview (see Anand and Cochrane, 2005;Platt, 2007;Gater et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Balarajan, Yuen, and Raleigh (1989) found that after adjusting for age and socio-economic group, consultation rates among men and women of Pakistani origin were almost three times and double, respectively, compared to the indigenous men and women. Anand and Cochrane (2005) argued that one reason for British Asians appearing more resilient is that Western diagnostic classification systems fail to understand and diagnose Asians experience and presentation of distress.…”
Section: Introductionmentioning
confidence: 98%
“…D'une manière générale, les études qualitatives tentant de rendre compte des différents itinéraires thérapeutiques des immigrants indiens soulignent que ces méthodes sont systématiquement perçues comme étrangères à la réalité socioculturelle des répondants et à leur conception de la détresse comme phénomène avant tout contextuel et appelant à un travail sur soi. Toutefois, la littérature qui traite de l'expérience de la détresse chez les migrants indiens au Canada demeure des plus marginales, un fait étonnant considérant que les études qui touchent directement le rapport des immigrants indiens à la santé mentale se comptent par dizaines en Angleterre (Anand et Cochrane 2005;Beliappa 1991;Burr et Chapman 2004;Dein et Sembhi 2001;Hussain et Cochrane 2004;Hussain et Cochrane 2003). Je discuterai d'ailleurs briè-vement les résultats de la présente recherche à la lumière d'une telle littéra-ture plus loin dans cet article.…”
Section: Introductionunclassified